The Effect of Dandang Gendis Extract (Clinacanthus nutans) on Kidney Histopathological Features of Diabetic Rats Model - Miranda Jemyma Mas'ulun; Arifa Mustika; Ema Qurnianingsih (Humanistic Network for Science and Technology (HNST), 2021)
Changes in kidney homeostasis due to diabetes can cause oxidative stress which then caused tissue damage that leads to diabetic nephropathy. Clinacanthus nutans extract is known to contain antioxidants that are reported to play an important role in the body’s defense system against oxidative stress to minimize tissue damage. This study aims to know the effect of Clinacanthus nutans leaf extract administration on kidney histopathological features of the diabetic rats model. A total of 35 rats were induced by streptozotocin which then divided into 5 groups and given Clinacanthus nutans extract with a dose of 75 mg/kgBW, 150 mg/kgBW and 300 mg/kgBW then compare with CMC-Na as control and metformin as standard drug for 14 days. The kidney histopathology was evaluated under a light microscope against the damage criteria that occurred in the proximal tubules of the kidney. As the result the least amout of kidney damage was on treatment group at dose 300 mg/kgBW, followed by extract with dose 75 mg/kgBW, 150 mg/kgBW, and metformin. In conclusion Clinacanthus nutans extract with a dose of 75 mg/kgBW, 150 mg/kgBW, and 300 mg/kgBW can improve the kidney histopathological feature of the diabetic rats model. Keywords: diabetes mellitus; histopathology; diabetic nephropathy; Clinacanthus nutans